Literasi Keuangan Digital Sebagai Upaya Pencegahan Penipuan Perbankan dan Mitigasi Kebocoran Data Pribadi - Irian Diana, Mila; Wikartika, Ira (Al-Khidmah Jurnal Pengabdian Masyarakat, 2025)
The development of digital technology has had a significant impact on the banking industry, especially in transaction patterns and financial management. However, this progress is also accompanied by an increase in cybercrime risks, such as banking fraud and personal data breaches. The low level of digital financial literacy among students makes this group more vulnerable to various modes of banking fraud. This program aims to improve the digital financial literacy of students as an effort to prevent banking fraud and mitigate personal data breaches. The activities were conducted through mini seminars and interactive discussions, providing materials that included education on the use of secure passwords, identification of fraud schemes, and steps to mitigate data breaches. The results show that 76.7% of students have a better understanding of digital financial literacy and the importance of personal data protection. With a better understanding of the risks and preventive measures, students are more prepared to face digital threats when using banking services.